VIOLENCE AND MURDER DONE BY JACK IN WILLIAM GOLDING’S LORD OF THE FLIES: Violence, Murder - Risma Kartika Dewi; Lailatul Afivah (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2022)
Violence and murder have a very bad impact on other people. Violence causes a person to be mentally disturbed and makes a person traumatized by the actions they have experienced. murder is a very frightening event and a phenomenon that is difficult to forget if the incident is in front of us, occurs suddenly. Murder causes a person to be injured and lose their life tragically at the same time. The researcher analyses two main problems, namely how the description of violence and murder that occurs in the novel and the factors that influence it. This thesis uses a qualitative descriptive research method. The data is taken from quotations in the novel and related to the theory and these quotations will serve as evidence for analysis. The researcher uses the theory of violence and homicide taken from several research journals to analyze the data. The results of the study indicate that there are several important factors that influence the occurrence of acts of violence and murder, namely anger and frustration experienced by the characters in the novel.